Topic Modeling of Discussions in the Standing Committees of the Brazilian Chamber of Deputies - dos Santos, Matheus A.; Andrade, Nazareno; Morais, Fabio (Journal of Information and Data Management, 2023)
In order to establish and reinforce democracy, civil society must have the ability to oversee and keep track of the actions of its representatives. Despite substantial progress in transparency, monitoring the committees of the Brazilian National Congress remains a challenge. Primarily, due to the large volume of activities in these committees and the lack of structured data on their discussions. This work provides two contributions to this context. The first is an open dataset containing structured speeches from the 25 standing committees of the Brazilian Chamber of Deputies over the past two decades, which we have created and made available. The second is the application of Natural Language Processing techniques, particularly Latent Dirichlet Allocation (LDA), to identify the topics addressed in these committees. Based on these latent topics, we studied the similarities and differences between the standing committees, their relations, and how their debates changed over time. We also explored how the speeches of parliamentarians from various political parties and states related differently to these latent topics. Our results demonstrate how the topics discussed in the standing committees reverberate external events and show that these committees accommodate conversations between their main topics and opposing agendas.